Биоморфологические особенности и жизненный цикл Veronica armena Boiss. et Huet. при интродукции в Донбасс - Кряж, Н.А. (Промышленная ботаника, 2002)
The account is given on the results of studying the ornamental and morphological peculiarities, rhythm of development and life-cycle of Veronica armena Boiss. et Huet. It is ascertained, that the species introduction into Donbass is successful. Its lifecycle is 6–7 years, the plant is the most ornamental in its 4–5 years. Preserving its ornamental qualities requires division of the schrub in the 4–5 years. It can be used for spring and autumn flowerbeds, in rockaries and natural flora gardens.